2017
DOI: 10.2147/ccid.s135441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of two volumizing hyaluronic acid dermal fillers in a controlled, randomized, double-blind, split-face clinical study

Abstract: BackgroundEnhancement of the midface can be achieved with volumizing hyaluronic acid (HA) fillers.ObjectiveThe objective of this study was to compare the safety and effectiveness of Cohesive Polydensified Matrix® 26 mg/mL HA gel (CPM-26) and Vycross® 20 mg/ml HA gel (VYC-20) in a controlled, randomized, evaluator-blind, split-face clinical study.Patients and methodsSubjects with moderate-to-severe malar volume loss on the Merz Aesthetics Scale (MAS) received CPM-26 on one side and VYC-20 on the contralateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 21 publications
5
31
0
Order By: Relevance
“…The duration of effects for hyaluronic acid fillers has been reported at 3 to 12 months, 1 year,18 months, and 2 years . A recent study of the use of injectable hyaluronic acid gel to correct volume loss of facial temporal fossa showed that the effects of the gel persisted at least 12 months in 98% of subjects .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of effects for hyaluronic acid fillers has been reported at 3 to 12 months, 1 year,18 months, and 2 years . A recent study of the use of injectable hyaluronic acid gel to correct volume loss of facial temporal fossa showed that the effects of the gel persisted at least 12 months in 98% of subjects .…”
Section: Discussionmentioning
confidence: 99%
“…The current study presented the patient-reported outcomes data from a single-center, randomized, controlled, split-face study that was also designed to evaluate the effectiveness and safety of CPM-26 compared with VYC-20. 13 , 14 The results of live assessment using the Merz Aesthetics Scale showed optimal correction for both products at visit M3 and longevity of the aesthetic effect up to M18. 14 Both products were also well tolerated.…”
Section: Discussionmentioning
confidence: 92%
“…According to the results of the blinded evaluator, 14 a volumizing effect was still present in more than half of the subjects with both products at M18, illustrating the longevity of the products. Based on MAS and GAIS ratings by the blinded evaluator and 3D volume assessment, CPM-26 showed a better performance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations